1999
DOI: 10.1002/(sici)1099-1611(199905/06)8:3<191::aid-pon355>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Exercise in the rehabilitation of breast cancer survivors

Abstract: With the increase in the number of women who have survived breast cancer, there is a growing need to attend to the physical and emotional effects of cancer and its treatment as experienced by these survivors. Psychological distress, fatigue, weight gain, premature menopause and changes in body image are some of the long‐term sequelae of breast cancer. Exercise as an adjunctive treatment may help to attenuate these effects and thereby contribute to rehabilitation of women with breast cancer. We present data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
65
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(68 citation statements)
references
References 52 publications
0
65
0
Order By: Relevance
“…Many symptoms that influence poor QoL in head and neck cancer patients are similar to those found in other cancer patients to be beneficially influenced by physical activity interventions [11,15,20]. For example, the most frequent psychological symptoms include worry, anxiety, mood disorders, fatigue, and depression, and the potentially disfiguring nature of the treatment may damage body image and self-esteem [10].…”
Section: Introductionmentioning
confidence: 92%
“…Many symptoms that influence poor QoL in head and neck cancer patients are similar to those found in other cancer patients to be beneficially influenced by physical activity interventions [11,15,20]. For example, the most frequent psychological symptoms include worry, anxiety, mood disorders, fatigue, and depression, and the potentially disfiguring nature of the treatment may damage body image and self-esteem [10].…”
Section: Introductionmentioning
confidence: 92%
“…Exercise has been found to be a safe method for enhancing HRQL among cancer patients [11] and increasing self-esteem in healthy populations [12,16,17,26,33,34,36]. In breast cancer survivors, four studies have demonstrated positive relationships between physical activity and self-esteem [4,27,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…This preliminary evidence suggests that physical exercise is a nonpharmacological behavioral intervention that shows great promise in mitigating the side effects experienced by cancer patients, both during and after receiving treatment, as well as improving QOL. Specifically, exercise is suggested to improve fatigue, QOL, emotional distress, immunological parameters, aerobic capacity, muscular strength, flexibility, and body composition among cancer survivors during and after treatment [3,8,9,11,14,15,18,19,[21][22][23][24][25][26][27]. Unfortunately, most studies have been small (averaging 50 patients and ranging from 9 to 155 participants [11,14,27]), single institution, intervention studies.…”
Section: Introductionmentioning
confidence: 99%